Development of Evidenced-Based Guidelines for PCOS and Implications for Community Health - Misso, Marie; Boyle, Jacqueline; Norman, Robert; Teede, Helena (Seminars in Reproductive Medicine, 2014)
Despite the prevalence and health implications of polycystic ovary syndrome (PCOS), key evidence practice gaps exist including delayed diagnosis, inconsistent management, inadequate support for lifestyle change, and limited attention to psychological and metabolic features. Key contributors to these gaps include a lack of awareness and absence of evidence-based guidelines (EBGs) to inform consumers and health professionals. Intervention was needed to improve awareness, patient experience, early diagnosis, self-management, complication screening, and treatment across reproductive, metabolic, and psychological features driving the authors to establish a national PCOS Alliance. All relevant stakeholders including consumers, researchers, and clinicians codeveloped a vision and based on compellingly need and lobbying, the Australian government funded development of EBGs meeting international standards. To maximize impact, a national dissemination and implementation program was delivered with ongoing evaluation. Activities were recognized by the U.S. National Institute of Health and are being scaled up with the World Health Organization.
Keywords: polycystic ovary syndrome; evidence-based guidelines